The Societal Impacts of Covid-19: A Transnational Perspective - Bozkurt, Veysel; Dawes, Glenn; Gulerce, Hakan; Westenbroek, Patricia (Istanbul University Press, 2021)
The COVID-19 Pandemic, started in China and has since spread all over the world in a short time, deeply affecting all countries.. Most countries have declared a partial or complete lockdown to limit the spread of the virus. A significant portion of employees have been unable to work in traditional ways and have had to adapt to what has become known as the "new normal". In essence we have gone beyond the norms we used to know and have had to contruct new ways of living in the times of COVID-19. The way we know how to work and live has changed. Middle and upper classes, whose jobs are suitable for digitalization, started working online. Every extraordinary period has its winners and losers. The winners of the coronavirus pandemic period were mainly hygiene materials manufacturers, gaming companies, electronic commerce, high technology, and pharmaceutical companies etc. On the other hand, economies all over the world have shrunk. The hardest hit in the pandemic have been the areas oftourism, hospitality and entertainment etc. resulting in high rates of unemployment or underemployment within these sectors. Unemployment and existential anxiety have peaked during 2020 with increased fears posed by the new risks associated with becoming infected. With th the loss of loved ones and separation from friends and family. Psycho-social problems have also increased due to the effects of prolonged uncertainty imposed by the pandemic across all facets of everyday life In all life satisfaction has declined across in all social groups with the vulnerable most at risk due to the long lasting effects on the pandemic. While the virus has impacted on the people from all social stratas, its effects have not been felt evenly. Poverty has deepened in most countries with large rises in unemployment and governments going into more debt to buffer their economies from the effects of the pandemic In addition to higher rates of unemployment, and greater economic uncertainty communication problems have also increased. The poor, the unemployed, those with limited education and some women were more severely affected than others. In this process, the problems experienced by particularly vulnerable groups are more severe than others. The uncertainty created by the pandemic has deeply shaken people's feelings of trust. Increased existential anxieties about life have weakened people's analytical thinking skills. There has also been a significant correlation between low trust and people's beliefs in conspiracy theories. Conspiracy theories have spread more easily in societies with low trust levels. The weaker the sense of trust that binds a society , the more people are likely to adhere to conspiracy theories in that country. This book, prepared with the contributions of authors from different countries, consists of sixteen chapters in total. The aim of the book is to examine the impact of the COVID-19 pandemic on societies. The first chapter titled "Unprecedented? Pandemic Memory and Responses to COVID-19 in Australia and New Zealand" was written by Claire Brennan and Patrick Hodgson. This chapter examines the common collective amnesia that surrounds pandemics, and compares the level of collective memory of the 1918-1920 influenza pandemic in Australia and New Zealand before the arrival of Covid-19. It scrutinizes government statements and actions while preparing for and responding to pandemics, the nurturing of historical knowledge among medical experts, and the actions of groups of citizens. Additionally, the section analyzes the importance of collective memory in designing effective responses to Covid-19 in these two countries.